Integrating Local Cultural Values in Character Education: An Integrative Literature Review within the Indonesian Educational Context - Rahmawati, Ilha (PT. Batari Edu Calya, 2025)
This study explores the integration of local cultural values into character education through an integrative literature review approach. Grounded in recent frameworks for educational and cultural studies, this research synthesizes findings from academic sources published between 2015 and 2024 to examine how indigenous wisdom strengthens moral and civic development in students. The analysis identifies three dominant models—Transmission, Participatory, and Transformative—each contributing distinctively to embedding cultural values in learning practices. The Transformative Model emerges as the most effective, fostering reflective, empathetic, and socially aware learners. Findings also highlight the crucial roles of educators, communities, and policymakers in ensuring that local wisdom becomes an intrinsic part of the educational process. Despite its potential, implementation challenges persist, including limited teacher competencies, insufficient cultural resources, and the erosion of traditional values amid globalization. The study recommends targeted teacher training, curriculum reform, and stronger collaboration with cultural stakeholders. By positioning local culture as the foundation of character education, Indonesia can cultivate globally competitive yet culturally grounded citizens who embody moral integrity and national identity. This integration aligns with the Merdeka Belajar initiative and contributes to the preservation of Indonesia’s diverse cultural heritage in the modern educational landscape.